The Prognostic Value of Perioperative Factors on Biochemical Recurrence in Patients Undergoing Radical Prostatectomy - Pyrgidis N; Weinhold P; Schulz GB; Chaloupka M; Berg E; Westhofen T; Rodler S; Keller P; Jokisch F; Stief CG; Marcon J; Bischoff R (Research and Reports in Urology, 2025)
Nikolaos Pyrgidis,* Philipp Weinhold,* Gerald Bastian Schulz, Michael Chaloupka, Elena Berg, Thilo Westhofen, Severin Rodler, Patrick Keller, Friedrich Jokisch, Christian G Stief, Julian Marcon, Robert Bischoff Department of Urology, University Hospital, LMU Munich, Munich, Germany*These authors contributed equally to this workCorrespondence: Nikolaos Pyrgidis, University Hospital LMU Munich, Department of Urology, Marchioninistraße 15, Munich, 81377, Germany, Tel +0049 152 5484 7591, Fax +49 89 4400 78890, Email Nikolaos.pyrgidis@med.uni-muenchen.deIntroduction: We aimed to assess the role of major perioperative risk factors (age, preoperative PSA values, body mass index, pathologic T-stage, resection status, and ISUP grade) in predicting biochemical recurrence (BCR) and survival after radical prostatectomy (RP) for prostate cancer (PC).Methods: An analysis of the prospective cohort of patients undergoing RP from 2013 to 2023 at our center was performed. Patients who received neoadjuvant or adjuvant therapies for PC or those with PSA persistence after RP were excluded. A Cox regression analysis was undertaken to evaluate the effect of major perioperative risk factors on the time to BCR. The role of the EAU BCR risk stratification on survival was also assessed. For all analyses, hazard ratios (HRs) with the corresponding 95% confidence intervals (CIs) were estimated.Results: A total of 1539 patients underwent RP for localized PC. At a median follow-up of 39 months (IQR: 25– 60) from RP, 393 (26%) patients developed BCR. Of them, 266 (68%) were classified as EAU BCR high risk and 127 (32%) as EAU BCR low risk. In the multivariate Cox regression analysis, locally advanced PC (HR: 1.5, 95% CI: 1.2– 1.9, p< 0.001), positive surgical margins (HR: 1.4, 95% CI: 1.1– 1.7, p=0.01), as well as ISUP grade 3 (HR: 2.4, 95% CI: 1.5– 3.6, p< 0.001) and 4 (HR: 2.4, 95% CI: 1.5– 3.7, p< 0.001) were associated with worse time to BCR. Overall, 16 (1%) patients died. Of them, 13 (81%) were classified as EAU BCR high risk and 3 (19%) as EAU BCR low risk (p< 0.001). In the univariate Cox regression analysis, patients with EAU BCR high risk presented worse overall survival (HR: 4.9, 95% CI: 1.4– 17, p=0.014).Conclusion: Locally advanced PC, positive surgical margins, and worse ISUP grade are independent risk factors for BCR. Accordingly, patients at BCR high-risk based on the EAU risk stratification present worse overall survival.Keywords: prostate cancer, prostatectomy, overall survival, biochemical recurrence